(untitled) (International Journal of Studies in Nursing, 2021)
Aim: To identify risk factors for weight gain after two years of a breast cancer diagnosis. Background: Obesity in survivors of early-stage breast cancer has been associated with high disease recurrence rates and lower overall survival rates. Continuous weight gain is an indisputable phenomenon. Identifying factors at the early diagnosis and treatment phase that are associated with weight gain at 2 years later may help to develop further intervention for prevention obesity in breast cancer survivors. Method: A retrospective study was designed to review medical records of 1901 early-stage breast cancer survivors. Extracted data included demographics, past medical history, cancer treatment, tumor characteristics, BMI at diagnosis, and 24-month weights. Results: The sample had a mean age 50.3 (+10.7). Most of them were premenopausal, stage II and BMI ranging from 18.5 to 24 kg/m2 at diagnosis. A majority of them received mastectomy (65.9%), chemotherapy (68.8%), radiotherapy (64.6%) and hormone therapy (63%). At 24 months after surgery, the breast cancer patients gained a mean of 0.4kg; but 21.6% of them gained 5% or more. The breast cancer survivors those who were premenopausal at diagnosis, less-than-high-school education, receiving adriamycin agent, cyclophosphamide agent, and gaining 5% or more weight after surgery had significant higher risk to gain 5% or more at 2 years after diagnosis. Conclusion: Findings from our study suggested that the premenopausal women or those who receive less formal education have higher risk to gain weight after breast cancer treatment. Engagement to healthy weight management for these high risk groups are warranted